The Impact of New Technologies and Political-Economic Systems on Public and Private Debt in the Context of Industrial Revolution 4.0 - Rodica Gherghina; Emilia Mioara Câmpeanu; Florin Văduva; Ioana Duca; Mirela Anca Postole; Robert-Adrian Grecu (Amfiteatru Economic)
The era of debt, in the context of the Industrial Revolution 4.0, imposes the need to investigate how improvements in public and private debt can be achieved. This paper analyses the impact of the new technologies and political-economic systems on the economy reflected through the public debt of the European Union countries, under the impetus of the Industrial Revolution 4.0, using panel regression models doubled by causality tests to provide robustness to the findings. The results confirm different effects in the public and the private sector as the political-economic systems, through macroeconomic factors, significantly influence the public sector comparing to the private sector, in terms of debts. Moreover, through governance indicators, the political-economic systems have varying impacts depending on the time horizon. At the same time, an increase in the presence of new technologies in the economy has a much faster and stronger effect on the dynamics of private debt. Thus, the research results support economic liberalism to the detriment of statism, by continuing the efforts of public institutions and companies to open up to investment in order to benefit from the effects of the Industrial Revolution 4.0, provided that the sustainability of accumulated debt is ensured.